Purification and characterization of a hyaluronidase from venom of the spider Vitalius dubius (Araneae, Theraphosidae) - Sutti,Rafael (2014)
BackgroundVenom hyaluronidase (Hyase) contributes to the diffusion of venom from the inoculation site. In this work, we purified and characterized Hyase from the venom of Vitalius dubius (Araneae, Theraphosidae), a large theraphosid found in southeastern Brazil. Venom obtained by electrical stimulation of adult male and female V. dubius was initially fractionated by gel filtration on a Superdex® 75 column. Active fractions were pooled and applied to a heparin-sepharose affinity column. The proteins were eluted with a linear NaCl gradient.ResultsActive fractions were pooled and assessed for purity by SDS-PAGE and RP-HPLC. The physicochemical tests included optimum pH, heat stability, presence of isoforms, neutralization by flavonoids and assessment of commercial antivenoms. Hyase was purified and presented a specific activity of 148 turbidity-reducing units (TRU)/mg (venom: 36 TRU/mg; purification factor of ~4). Hyase displayed a molecular mass of 43 kDa by SDS-PAGE. Zymography in hyaluronic-acid-containing gels indicated an absence of enzyme isoforms. The optimum pH was 4-5, with highest activity at 37°C. Hyase was stable up to 60°C; but its activity was lost at higher temperatures and maintained after several freeze-thaw cycles. The NaCl concentration (up to 1 M) did not influence activity. Hyase had greater action towards hyaluronic acid compared to chondroitin sulfate, and was completely neutralized by polyvalent antiarachnid sera, but not by caterpillar, scorpion or snakes antivenoms.ConclusionThe neutralization by arachnid but not scorpion antivenom indicates that this enzyme shares antigenic epitopes with similar enzymes in other spider venoms. The biochemical properties of this Hyase are comparable to others described.